Pancreatic neuroendocrine tumors: classification, diagnosis and treatment - A review of the most frequent neuroendocrine tumors - Dominika Karolina Adamiec; Marta Justyna Gonciarz; Anna Dąbrowska; Dominika Zaliwska; Monika Kienanh Do; Agnieszka Aleksandra Strojny; Natalia Paduszyńska; Adrianna Kraszkiewicz; Monika Anna Kamińska; Magdalena Czach (Nicolaus Copernicus University in Toruń, 2024)
Neuroendocrine tumors (NETs) are a heterogeneous group of tumors originating from cells of the dispersed endocrine system. They vary in their degree of differentiation and malignancy. They are primarily located in the gastrointestinal tract, pancreas, and lungs. This article will present the most common pancreatic neuroendocrine tumors, their specific characteristics, diagnostic methods including imaging diagnostics, and treatment options. NETs account for approximately 0.5% of all malignant tumors. Pancreatic neuroendocrine tumors include insulinoma, gastrinoma, glucagonoma, vipoma, and somatostatinoma. They secrete hormones specific to each type, chromogranins, and pancreatic polypeptide. However, only some of these tumors have a secretory function. They are usually well-differentiated tumors. Neuroendocrine tumors are difficult to diagnose due to their specific nature. They are typically diagnosed at an advanced stage, except for insulinoma. The most commonly used imaging methods are CT, MRI, PET, and SPECT. Treatment is extremely challenging due to symptoms caused by excessive hormone secretion. Usually, the first step in treatment is to alleviate symptoms. The only curative option is the removal of the tumor and its metastases. Unfortunately, this option is not available for many patients due to the late detection of the disease. Currently, many methods are used to slow the progression of tumors, including peptide receptor radionuclide therapy, mTOR inhibitors (everolimus), sunitinib, and chemotherapy. Detection and treatment are extremely difficult due to the specific nature of this group of tumors.